Peranan Modal Sosial Islami dalam Pengembangan Pariwisata Lokal di Gunung Pawon Payangan Ambulu Jember - Lestari, Dwi Ayu; Siswanto, Adil (Lembaga Teewan Journal Solutions, 2026)
This study aims to analyze the role of Islamic social capital in the development of local tourism in Gunung Pawon, Payangan, Ambulu, Jember. The research uses a qualitative descriptive approach to explore how Islamic values such as trust (amanah), norms (shura), reciprocity (ta’awun), social networks (silaturahim), and shared goals (ukhuwah Islamiyah) are applied in community-based tourism management. Data were collected through observation, interviews, and documentation involving tourism managers, MSME actors, and visitors. The findings show that Islamic social capital plays a crucial role as the foundation of tourism management, strengthening cooperation, transparency, and community participation. Trust builds openness in management, norms guide collective decision-making, networks support promotion and communication, reciprocity enhances economic benefits for local communities, and shared goals unite stakeholders in developing sustainable tourism. Overall, Islamic social capital contributes significantly to the sustainability of Gunung Pawon tourism by fostering harmony, economic empowerment, and community-based development.